To simplify the expression \((4x^4y^{-4})^3 (x^7y^3)^2\), we will apply the properties of integer exponents.
-
Simplify each part separately:
\((4x^4y^{-4})^3 = 4^3 (x^4)^3 (y^{-4})^3\)
- \(4^3 = 64\)
- \((x^4)^3 = x^{12}\)
- \((y^{-4})^3 = y^{-12}\)
Therefore, \((4x^4y^{-4})^3 = 64x^{12}y^{-12}\).
-
Now simplify the second part:
\((x^7y^3)^2 = (x^7)^2 (y^3)^2\)
- \((x^7)^2 = x^{14}\)
- \((y^3)^2 = y^{6}\)
Therefore, \((x^7y^3)^2 = x^{14}y^6\).
-
Now, combine the two simplified parts:
\[ (64x^{12}y^{-12})(x^{14}y^{6}) = 64x^{12+14}y^{-12+6} \]
Simplifying the exponents:
- For \(x\): \(12 + 14 = 26\)
- For \(y\): \(-12 + 6 = -6\)
This gives us: \[ 64x^{26}y^{-6} \]
-
We can express \(y^{-6}\) as \(\frac{1}{y^6}\):
\[ 64x^{26} \cdot \frac{1}{y^6} = \frac{64x^{26}}{y^6} \]
Thus, the simplified expression is:
\[ \frac{64x^{26}}{y^6} \]
None of the answer choices exactly match this result. However, if the expression options you provided included \(\frac{64x^{2}y^{18}}{1}\), that might suggest that perhaps there was a misunderstanding or error in the exponent calculations.
Please check the options against the expression we derived to find a correct match.